PERAN DEWAN PENDIDIKAN DALAM PERCEPATAN PENINGKATAN KUALITAS PENDIDIKAN SEKOLAH MENENGAH DENGAN MENGOPTIMALKAN KOMPETENSI KEPALA SEKOLAH DI PROVINSI RIAU - Nurfaisal Nurfaisal (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This study examined the education board's role in accelerating the improvement of the school principals' competence in Riau province. Development in education is one of the keys to the success of national growth. The principal is required to lead the school into a quality school following the demands of the current expansion of science and technology so graduates can be accepted at well-known universities domestically and abroad.The education council is a community organization that has commitment and loyalty and oversees improving the education quality in the region. As an independent institution, the education council will improve education services by providing development, direction, and support, personnel for facilities and infrastructure, and education supervision at the national, provincial and district/city levels. To realize this improvement in the school principals' competence, the Riau education board must synergize with the education office since various criticisms and suggestions are always proposed by the community, parents and students' guardians through this education board who come from people with educational backgrounds, concern about education, even from people who have managed education, so that they will know the intricacies and strategies for improving the competence of the principal. By optimizing the education board's role, the improvement of the principal's competence will be realized, so the schools in Riau are of high quality, and their graduates can be accepted in numerous well-known universities as the next generation of development staff and development in the Riau province.